2012
DOI: 10.5755/j01.itc.41.4.1108
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Extraction of Features and Generation of Feature Models from Java Programs

Abstract: Feature modelling is a key technique for identifying common and variable features in software (software component families). The result of feature modelling is a feature model: a concise specification of product features and their relationships. Feature models have been proven to be useful for software variability modelling and management. However, there is a wide gap between feature models and program source code. Here we focus on reverse engineering of source code to feature models. We present a framework fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The sixth scenario was extracted from [Chen et al 2005] In this scenario, only the clustering technique was used, making it the most common retrieval technique up to this point. The seventh scenario was defined by extracting the information from [Paškevičius et al 2012]. The clustering and dependency analysis techniques were present once again.…”
Section: Scenario's Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sixth scenario was extracted from [Chen et al 2005] In this scenario, only the clustering technique was used, making it the most common retrieval technique up to this point. The seventh scenario was defined by extracting the information from [Paškevičius et al 2012]. The clustering and dependency analysis techniques were present once again.…”
Section: Scenario's Resultsmentioning
confidence: 99%
“…Despite the great number of studies on the topic of SPL reengineering [Assunc ¸ão et al 2017, Laguna andCrespo 2013], we observed limitations that motivated us to propose PAxSPL. Firstly, the studies in the literature mostly focus on technical aspects of the variants, namely identification of commonalities and variabilities among variants implementation [Eyal-Salman et al 2013, Paškevičius et al 2012, without taking into account organizational aspects, e.g., team experience. Considering only technical aspects hampers the application of the SPL reengineering process in real-world scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Reverse engineering [31,34,36,39,48,54,56,70,86,126,127,131,134,144,148,149,151,157,163,164,180,181,191,215,233,244,268] 27…”
Section: Variability Contextmentioning
confidence: 99%
“…Citations #papers Opinion Paper [66,73,75,144,164,193,248] 7 Philosophical Paper [51,74,99,101,134,137,171,175,196,201,244] 11 Solution Proposal [30,35,44,58,60,65,72,78,79,80,81,93,102,106,140,141,142,145,151,158,162,165,172,176,184,185,191,195,197,198,199,200,203,…”
Section: Research Facetmentioning
confidence: 99%
“…Feature models (FM) are widely used to describe variability among applications for a given domain, by specifying features and their interdependencies. A feature is typically referred to as an increment in functionality [10,11] and the following relationships among features are supported (see Fig. 1a): mandatory features-child features that must always appear with their parents; optional features-child features that optionally appear with their parents; alternative feature groups-a group of features from which only one can be included in any application; and or feature groups-a group of features that are optional, but at least one needs to be selected.…”
Section: Feature Modelmentioning
confidence: 99%